„WYJRZAŁEM W ZA-ŚWIAT”. KILKA UWAG O TRADYCJI ROZMÓW ZMARŁYCH W TWÓRCZOŚCI CYPRIANA NORWIDA - Seweryn, Agata (Colloquia Litteraria, 2017)
“Wyjrzałem w za-świat” [I Glanced into the Nether-world]. Some Remarks on the Tradition of the Conversations among the Dead in Cyprian Norwid’s Works The study focuses on the tradition of the conversations among the dead in Cyprian Norwid’s works, especially in the poem Vendôme. While noting Norwid’s transformations of classical and classicist conventions, the author points to the mannerist and baroque contexts, and on the other hand, to ekphrastic qualities of Norwid’s literary imagination.